Students’ Perceptions of Project-Based Learning in Writing English Procedure Texts - Anti Mardiana; Adib Ahmada (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to determine the perceptions of seventh-grade students at MTs Roudlotul Muta'alimin regarding the application of Project-Based Learning (PjBL) through posters in writing English procedural texts. This study employed a descriptive research design using a case study approach, with data collected through open-ended questionnaires completed by 20 students and semi-structured interviews with five selected students. . Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The findings indicate that students generally have a positive perception of the implementation of PjBL through posters. Students consider this approach to encourage active engagement in the learning process, increase confidence in writing English procedural texts, and make learning more enjoyable and meaningful. Although students experience linguistic challenges, especially in vocabulary selection and sentence construction, these difficulties are considered surmountable with proper teacher guidance and structured learning activities. Overall, this study concludes that Project-Based Learning through posters is considered an effective instructional approach for teaching English procedural writing at the junior high school level and provides valuable insights for English teachers in implementing student-centered learning practices.